2002
DOI: 10.1080/00224490209552117
|View full text |Cite
|
Sign up to set email alerts
|

Influences of culture on Asian Americans' sexuality

Abstract: Asian Americans comprise a population group that is characterized by an enormous demographic, historical, and cultural heterogeneity, yet Asian Americans also share many Asian cultural characteristics such as the primacy of the family and the collective's goals over individual wishes, emphasis on propriety and social codes, the appropriation of sexuality only within the context of marriage, and sexual restraint and modesty. Although there are significant gaps in the scientific literature concerning Asian Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 49 publications
8
184
2
3
Order By: Relevance
“…Moreover, Huang and Uba (1992) found that Chinese American women were more sexually experienced and more likely to be currently involved in a relationship than were Chinese American men of the same age. Given that sexual restraint and modesty are often viewed as characteristic to a degree of East Asian cultures (see Okazaki, 2002), greater sexual experience among bicultural female Chinese Americans may be seen as an indicator of low traditionalism. Suggested reasons for these findings of lower traditionalism among female East Asian immigrants include faster acculturation among females than males (Mok, 1999) and female immigrantsÕ rebellion against social pressure to conform to heritage ideals of femininity (e.g., Dion & Dion, 2004).…”
Section: Gender -Another Cultural Layer In the Personal Relationshipsmentioning
confidence: 99%
“…Moreover, Huang and Uba (1992) found that Chinese American women were more sexually experienced and more likely to be currently involved in a relationship than were Chinese American men of the same age. Given that sexual restraint and modesty are often viewed as characteristic to a degree of East Asian cultures (see Okazaki, 2002), greater sexual experience among bicultural female Chinese Americans may be seen as an indicator of low traditionalism. Suggested reasons for these findings of lower traditionalism among female East Asian immigrants include faster acculturation among females than males (Mok, 1999) and female immigrantsÕ rebellion against social pressure to conform to heritage ideals of femininity (e.g., Dion & Dion, 2004).…”
Section: Gender -Another Cultural Layer In the Personal Relationshipsmentioning
confidence: 99%
“…The high unemployment levels in Nepal now may contribute to the dating of unmarried boys and girls sex with married partners to ease their financial problems, although pre-and extramarital sexual relations are still a taboo in Nepal (Dahal, 2008;Okazaki, 2002;Puri & Busza, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to Waszak and colleagues (2003: 83) "Girls "caught" talking to boys in public places are criticized and sometimes punished by parents and the community for being characterless." Hence, sexual activities before and outside marriage are often not acceptable (Dahal, 2008;Okazaki ). However, with increased exposure to global television and radio networks, movies and the modernisation of society and culture, the young generation has taken a more positive turn in terms of attitudes towards sexual relationships.…”
mentioning
confidence: 99%
“…Delivering sexual education through GBL is more likely to be harmless, comforting and supportive in cultures where talking about sex in public is taboo (Okazaki, 2002). This teaching and learning technique may promote skill transformation, such as problem solving and collaboration, which can be emphasized through GBL to promote sexual education among adolescents.…”
Section: The Role Of Gbl In Adolescent Sexual Health Educationmentioning
confidence: 99%
“…Insufficient skilled expertise (Hong Kong Department of Health, 2014), and 7. Taboos against socio-cultural values like speaking about sex in public in some countries (Okazaki, 2002).…”
Section: Globalmentioning
confidence: 99%